The Effects of Paracoccidioides brasiliensis Infection on GM-CSF- and M-CSF-Induced Mouse Bone Marrow-Derived Macrophage from Resistant and Susceptible Mice Strains - Calliandra de Souza Silva; Aldo Henrique Tavares; Marcio Sousa Jeronimo; Yasmin Soares de Lima; Lorena da Silveira Derengowski; Anamélia Lorenzetti Bocca; Ildinete Silva-Pereira (Hindawi Limited, 2015)
Considering the importance of macrophages as the first line of defense against fungal infection and the different roles played by the two M1- and M2-like polarized macrophages, we decided to evaluate the effects of Paracoccidioides brasiliensis infection on GM-CSF- and M-CSF-induced bone marrow-derived macrophages (BMM) from the A/J and B10.A mouse strains, an established model of resistance/susceptibility to PCM, respectively. Upon differentiation, the generated GM- or M-BMMs were characterized by morphological analyses, gene expression profiles, and cytokines production. Our main results demonstrate that GM-BMMs derived from A/J and B.10 produced high levels of pro- and anti-inflammatory cytokines that may contribute to generate an unbalanced early immune response. In accordance with the literature, the B10.A susceptible mice lineage has an innate tendency to polarize into M1-like phenotype, whereas the opposite phenotype occurs in A/J resistance mice. In this context, our data support that susceptibility and resistance are strongly correlated with M1 and M2 polarization, respectively.